Peran Guru Pendidikan Agama Islam Untuk Meningkatkan Kedisiplinan Siswa Melalui Sholat Berjamaah - Ali Ashar; Imam Fatoni; Hartoyo Hartoyo (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
Educational outputs are produced from the learning process, in learning it is necessary to plan and implement and evaluate various elements of education, no less important the role of a teacher, especially the teacher of Islamic Religious Education. The purpose of the research is to find out the role of Islamic Religious Education teachers to improve student discipline through congregational. The results of this study are: (1). PAI teachers encourage and direct students to participate in religious activities. (2) PAI teachers encourage observance of religion. (3) PAI teachers improve discipline by inspiring their students. (4) PAI teachers always give good examples to their students. (5) PAI teachers always try their best to do prayers in congregations.